Use of social media space for library service delivery: evidence from Southern Nigeria universities (2020)
The incorporation of social media into service delivery by librarians is essential to render contemporary and seem-less library services to the users. Studies have shown that awareness and perception constitute important factors in the use of emerging technology for personal use with paucity of literature on the use of social media for library service delivery. Therefore, this study was designed to investigate the use of social media for service delivery by librarians in Southern Nigeria universities. Survey research design was adopted for the study. The population of the study comprised 669 librarians from the universities in Southern Nigeria. Total enumeration technique was adopted for the study. Data collected were analysed using descriptive statistics. Findings revealed that librarians used very few social media space for delivering library services. Low bandwidth, culminated in slow internet connection was the main challenge to the application of social media. Recommendations such as increase in the use of social media space and the provision of robust bandwidth to enhance internet connectivity were proffered.